2022
DOI: 10.1371/journal.pone.0278777
|View full text |Cite
|
Sign up to set email alerts
|

Short stay hospital admissions for an acutely unwell child: A qualitative study of outcomes that matter to parents and professionals

Abstract: Background Numbers of urgent short stay admissions (SSAs) of children to UK hospitals are rising rapidly. This paper reports on experiences of SSAs from the perspective of parents accessing urgent care for their acutely unwell child and of health professionals referring, caring for, or admitting children. Methods A qualitative interview study was conducted by a multi-disciplinary team with patient and public involvement (PPI) to explore contextual factors relating to SSAs and better understand pre-hospital u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…We also found that people prefer to use EDs over GP clinics because GPs have limited interventions and equipment available. In line with this study, Butun et al [5] and Malcolm et al [26] found that patients had insufficient knowledge about GP clinics and how to use them appropriately. Improving primary health care services such as improving the physical conditions of buildings, medical equipment, and qualified staff should be considered as solutions for reducing nonurgent ED visits and, therefore, improving the quality of care.…”
Section: Discussionsupporting
confidence: 77%
“…We also found that people prefer to use EDs over GP clinics because GPs have limited interventions and equipment available. In line with this study, Butun et al [5] and Malcolm et al [26] found that patients had insufficient knowledge about GP clinics and how to use them appropriately. Improving primary health care services such as improving the physical conditions of buildings, medical equipment, and qualified staff should be considered as solutions for reducing nonurgent ED visits and, therefore, improving the quality of care.…”
Section: Discussionsupporting
confidence: 77%
“…For quantitative purposes, SSA can be defined as a patient being admitted and discharged on the same calendar day 1 2. For qualitative sampling, since some parents cannot recall the precise time of admission and discharge, SSA can be defined as where parents’ recall their child being admitted and discharged within 24 hours 3. The rate of hospital medical admissions for children with acute illness in Scotland rose by 49% between 2000 and 2013, with SSAs rising by 186% from 8.6 to 24.6/1000 children per annum 2.…”
Section: Introductionmentioning
confidence: 99%
“…And from those questions, about who should be listened to and the context of that evidence in making decisions about children and their care. "Nurses are often described as closest to their patients, due to the intimate nature of their practice" (Levy, 2023: 15).Given that the majority of admissions to children's units is approximately 24 hours (Malcolm et al, 2022), under these circumstances, the people closest to the children will almost certainly be the parents, which will most probably be the mother/prime carer. However, care needs to be taken with issues of 'ownership' of the child being dealt with subtlety and respect for both the rights of the parents and the child (Shields et al, 2003).…”
mentioning
confidence: 99%
“…Given that the majority of admissions to children's units is approximately 24 hours (Malcolm et al, 2022), under these circumstances, the people closest to the children will almost certainly be the parents, which will most probably be the mother/prime carer. However, care needs to be taken with issues of 'ownership' of the child being dealt with subtlety and respect for both the rights of the parents and the child (Shields et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation